IMPLEMENTASI PENDIDIKAN KEAKSARAAN DI KABUPATEN MAROS - ali ali (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2022)
The study aims to determine the picture of the implementation of literacy education in Maros district, seen in terms of planning, organizing, implementing learning, coordination, coaching and assessment as well as learning outcomes of learning residents. This research is a type of case study by usinga  combination of qualitative and quantitative research approaches.  Based on the results of the data analysis, conclusions were drawn (1) The literacy education program in Maros district has been implemented through a series of planning, organizing, implementing learning, coordination, coaching and assessment, as well as meeting basic literacy education standards, (2) the literacy education program is supported by the ranks of level II local governments, private institutions and illiterate citizens. In addition, there are still obstacles such as the slowness of disbursement of organizing funds from the government, the lack of tutoring in teaching citizens to learn and the lack of activity of citizens learning to participate in learning. (3) Learning outcomes in the form of literacy ability achieved by residents learning literacy education are more at a high level of achievement, in other words, that the literacy education program has succeeded in liberating illiteracy for illiteracy residents in Maros district